Effect of additional pollen supplement on fruit setting in Moringa oleifera - Frédéric, BAZIE Babou; Ebou, DAO Madjelia Cangré (Journal of Agriculture and Natural Resources, 2022)
Moringa oleifera Lam. is a woody species with hermaphrodite flowers cultivated for its fruits and seeds for oil production. The fruit production of the species remains below producers’ expectations.The current study was carried out from July to October along two consecutive years (2019 and 2020) at Komsilga (12°18’48.2’’N and 1°64’60.2’’W ) and at the INERA experimental station in Ouagadougou (12°22’801’’N and 1°30’295’’W ) both located in the northern Sudanian zone of Burkina Faso. Our study aimed at testing whether additional pollen on the flower stigma could improve pod and seed yields. For this purpose, a sample of 10 flowering trees and 20 inflorescences/tree was randomly selected at each site. Per tree, 10 newly flowering inflorescences were left to open pollinated and 10 others received pollenmanually. Results show that hand-pollinated inflorescences produced an average of 0.19 and 0.17 fruits, compared to 0.16 and 0.14 for open-pollinated inflorescences at INERA and Komsilga respectively (p= 0.7720). The mean seed weight was 63 (±11.2) and 50 (±7.4) g for the manualand open pollinated treatment, respectively. The Kruskal-wallis test of mean seed weight shows that the smallest fruits were obtained in the open pollination which differed significantly from manual pollination (p< 0.0001). The addition of pollen significantly improved Moringa fruit production.